Melhoria na gestão de estoque de material de expediente no setor público: Um estudo de caso na busca por eficiência e acuracidade - Barros, Miguel Miranda (Brasil, 2024)
This case study addresses the analysis and improvement in stock control of office materials in the public sector, with a focus on optimizing accuracy for high-turnover and value-added items. Efficient inventory management is essential for the smooth functioning of logistics operations, especially within the government context, where limited resources must be allocated strategically. In this study, the complexities of storing and distributing office materials are explored, highlighting challenges such as lack of visibility, excess inventory and the possibility of obsolescence. Through an analytical approach, the main gaps in the current inventory control process are identified, demonstrating the importance of technologies such as inventory management systems and automation. Through data analysis and demand forecasting techniques, a strategy is proposed to optimize the accuracy of stock levels, minimizing waste and maximizing the availability of materials when needed.